The Effectiveness of Hypnotherapy in Reducing Pain in Patients with Cervical Cancer - Prasetya, Hanung; Kusumawati, Heni Nur; Wardiyatmi, Wardiyatmi (Indonesian Journal of Medicine, 2021)
Background: Complaints of pain in cervical cancer patients make the patient suffer more. Pain is a subjective matter so that hypnotherapy can reduce the pain suffered by patients. The use of hypnotherapy in cancer patients focuses on the emotional aspects and dynamics that occur in the client's subconscious mind. Hypnotherapy can change sensations, perceptions, thoughts, feelings or behavior after being suggested. Positive suggestions given are able to influence the perception of someone who is in a hypnotic state so that they behave or perceive according to the suggestions given. The purpose of this study was to analyze the effect of hypnotherapy as a complementary therapy in reducing pain in cervical cancer patients.Subjects and Method: The experimental study used a random control trial which was conducted at the Dr. Moewardi Hospital from January to September 2019. A sample of 90 patients was selected by purposive sampling. 45 subjects from the treatment group received the hypnotherapy intervention and 45 subjects from the control group received standard care. The dependent variable is the level of pain. The independent variable is hypnotherapy. The level of pain is measured by a numerical pain scale of 0 to 10. Hypnotherapy is performed using hypnosis recording/ audio. Data analysis was performed using an independent t test.Results: The mean pain level after hypnotherapy (Mean= 0.8; SD= 1.96) was lower than the control group (Mean= 3.2; SD= 1.7), effect size= -1.31, and it was statistically significant (p <0.001).Conclusion: Hypnotherapy complementary therapy can help reduce pain levels in cervical cancer patients.Keywords: hypnotherapy, pain, cervical cancerCorrespondence:Hanung Prasetya. Study Program in Acupuncture, Health Polytechnics, Ministry of Health. Jl. Letjend Sutoyo, Mojosongo, Surakarta 57127, Central Java. Email: Hanungprasetya71@yahoo.com. Mobile: +628122638908.Indonesian Journal of Medicine (2021), 06(02): 152-158https://doi.org/10.26911/theijmed.2021.06.02.04